State estimation of power system with UPFC using interior point WLAV method - C. Rakpenthai (2018)
This paper presents a robust state estimator for power system containing unified power flow controller. The state estimation problem is formulated as an optimization problem using weighted least absolute value criteria, with a set of equality and inequality constraints. The interior point optimization method is applied to primal and dual formulation in order to solve this problem. The modified IEEE 14-bus system is used to demonstrate the effectiveness of the proposed algorithm. The simulation results indicate that the method yields good estimation of the system states for a power system with UPFC. © 2006 IEEE.